Erzählen vom Leben im 20. Jahrhundert Erinnerungspraxis und Erzähltraditionen in lebensgeschichtlichen Interviews am Beispiel der Region Montafon/Vorarlberg - Hessenberger, Edith (Studien Verlag, 2013)
Biographic narratives are shaped by many factors. The shape old people finally select for the retrospective view of their lives, is for example influenced by the current narrative situation, by the individual's perception of the past, or by the patterns of reconstruction. Using the example of 67 biographical narratives, the graduate thesis "Telling about life in the 20th Century" demonstrates, how cultural influences shape the practice of memory, and how narrative traditions ultimately decide on the form of autobiographical representation.